2022
DOI: 10.3390/cells11233719
|View full text |Cite
|
Sign up to set email alerts
|

NSCLC Cells Resistance to PI3K/mTOR Inhibitors Is Mediated by Delta-6 Fatty Acid Desaturase (FADS2)

Abstract: Hyperactivation of the phosphatidylinositol-3-kinase (PI3K) pathway is one of the most common events in human cancers. Several efforts have been made toward the identification of selective PI3K pathway inhibitors. However, the success of these molecules has been partially limited due to unexpected toxicities, the selection of potentially responsive patients, and intrinsic resistance to treatments. Metabolic alterations are intimately linked to drug resistance; altered metabolic pathways can help cancer cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…In ovarian cancer, inhibition of FADS2 directly downregulated GPX4 and the GSH/GSSG ratio, disrupted cellular/mitochondrial redox balance, and then leaded to iron-mediated lipid peroxidation and mitochondrial dysfunction in ascites-derived ovarian cancer cells ( 32 ). Another study indicated that FADS2 mediated resistance to PI3K/mTOR inhibitors in NSCLC ( 33 ). These findings suggest that the genes within this signature could potentially impact the prognosis of LUSC by regulating tumor lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In ovarian cancer, inhibition of FADS2 directly downregulated GPX4 and the GSH/GSSG ratio, disrupted cellular/mitochondrial redox balance, and then leaded to iron-mediated lipid peroxidation and mitochondrial dysfunction in ascites-derived ovarian cancer cells ( 32 ). Another study indicated that FADS2 mediated resistance to PI3K/mTOR inhibitors in NSCLC ( 33 ). These findings suggest that the genes within this signature could potentially impact the prognosis of LUSC by regulating tumor lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%